STEM Education Based On Smart Toys: 21st Century Learning - Haryadi, Rudi; Pujiastuti, Heni (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2021)
The 21st century is a century of knowledge where knowledge will become the main foundation of all aspects of life. The age of knowledge is very influential on education, science, technology, and employment. Technology is now a very important part of human life. Technology plays a major role in helping and facilitating humans in carrying out various activities in their lives. Technology education from an early age is also very important for children, one of which is STEM. The type of research method chosen is descriptive analysis, while the understanding of analytical descriptive method is a method that serves to describe or give an overview of the object under study through data or samples that have been collected as they are without doing analysis and making conclusions that apply to the public. Based on the results of the study, overall shows a positive response from students towards smart toys used in the learning process so that it can be used as an innovation in the learning process.